DAMPAK KEBERADAAN MASJID AR-RAHMAN KOTA BLITAR TERHADAP KONDISI SOSIAL-EKONOMI PELAKU BISNIS UMKM - Iqlima Shinta Fatmala; Muhammad Alhada Fuadilah Habib (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The existence of the Ar-Rahman Mosque which is located on Jalan Ciliwung, Bendo Village, Kepanjen Kidul District, Blitar City has its own uniqueness which is different from mosques in general. The uniqueness is in the form of an architecture similar to the Nabawi Mosque in Medina, so that the surrounding community and from outside are interested in visiting the Ar-Rahman Mosque, Blitar City. This is thought to have a positive impact on the surrounding community who have MSME businesses. This study aims to reveal the impact of socio-economic conditions felt by the surrounding community after the existence of the Ar-Rahman Mosque. The method used is descriptive qualitative. Data collection techniques were carried out through interviews, observation and documentation. In-depth interviews were conducted with MSME traders, visitors from the Ar-Rahman Mosque, people who live around the Ar-Rahman Mosque and managers from the Ar-Rahman Mosque. The results of this study indicate that the entire surrounding community is able to adapt to changes in socio-economic conditions after the existence of the Ar-Rahman mosque in Blitar City. They are capable of entrepreneurship by establishing micro, small and medium enterprises or MSMEs. The existence of the Ar-Rahman Mosque is able to improve the community's economy, the community can integrate with the mosque so that it has a positive impact on each other. The mosque tries to maintain the good values and norms that have been established between the community and the mosque management.